2020
DOI: 10.1016/j.ecoenv.2020.110367
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam impairs honey bee visual learning, alters decision times, and increases abnormal behaviors

Abstract: Learning is important for honey bee fitness and the pollination services that they provide. Neonicotinoid pesticides impair learning, fitness, colony health, and pollination, but most studies on how they affect bee learning have focused on olfactory learning. We tested the effects of field realistic doses of 0.8 ng/bee and 1.34 ng/bee of the neonicotinoid pesticide, thiamethoxam (TMX), on bee visual learning. We adapted a T-maze bioassay and classically conditioned bees to associate sugar reward with a simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…We found that exposure to imidacloprid had adverse effects on learning when bumblebees were subject to a combination of olfactory and visual stimuli, in contrast to studies that assessed visual stimuli only and that did not find any effect on learning (Colin et al, 2020;Lämsä et al, 2018;Ludicke & Nieh, 2020; but see Phelps et al, 2018). However, our findings align with studies on both olfactory and visual stimuli, showing that olfactory learning is impaired by imidacloprid exposure .…”
Section: Flower Visitssupporting
confidence: 66%
See 1 more Smart Citation
“…We found that exposure to imidacloprid had adverse effects on learning when bumblebees were subject to a combination of olfactory and visual stimuli, in contrast to studies that assessed visual stimuli only and that did not find any effect on learning (Colin et al, 2020;Lämsä et al, 2018;Ludicke & Nieh, 2020; but see Phelps et al, 2018). However, our findings align with studies on both olfactory and visual stimuli, showing that olfactory learning is impaired by imidacloprid exposure .…”
Section: Flower Visitssupporting
confidence: 66%
“…Assessing the effects of neonicotinoids on bee behavior and learning is a crucial step in understanding the impact these products might have on bee populations. Although most studies have focused on the effects of exposure to odor stimuli (Muth et al, 2019), visual stimuli have also been used in bumblebees (Lämsä et al, 2018; Muth & Leonard, 2019; Phelps et al, 2018) and honeybees (Ludicke & Nieh, 2020). However, there is a lack of multimodality studies that assess several stimuli and include social interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, even if the multimodal trap captured some Hymenopterans, we counted very few honeybees and bumblebees. In fact, blue wavelengths are non-preferential for these beneficial insects [ 71 , 72 ]. Conversely, several Lepidoptera were found inside blue-UV and green-UV traps, and it is known that UV and blue wavelengths, are particularly attractive for them [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are structurally similar to nicotine and target postsynaptic excitatory nicotinic acetylcholine receptors (nAChRs) of insects, causing paralysis due to overstimulation of neurons (Figures 1A,B) (7,36,47,48). When bees consume neonicotinoids, they can have severe problems in motor behaviors (49), in orientation and flight performance (34,(50)(51)(52)(53) and display severe learning deficits (54)(55)(56), among other adverse effects. It is astonishing that neonicotinoids are still considered as relatively safe for non-target organisms, given that numerous negative effects have been reported for a variety of organisms including birds and mammals.…”
Section: Insecticides Neonicotinoidsmentioning
confidence: 99%